Histopathological Spectrum of Phyllodes Tumor of Breast in a Tertiary Health Care Center: A 5-Year Retrospective Study - Parsa Kainat, Muhammad Rahil Khan, Sorath Sindhu, Riyasat Ahmed Memon, Zahid Ali Nohri, Maryam Anmol, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: This study was done to evaluate the histopathological spectrum of phyllodes tumor of breast in women of various age groups. Study design: Cross-sectional descriptive study Place and Duration: This cross-sectional study was done at the Department of histopathology, Liaquat University of Medical and Health sciences, Jamshoro, Pakistan. 2017-2021. Methods: Total 178 cases of phyllodes tumors were retrospectively identified. The clinical history of patients was taken from computer storage data followed by review of microscopic slides by two histopathologists. Excel 2021 and SPSS 22 were used for statistical analysis. Results: The mean age was 35.37 (range 12-70 years). Most of the cases were of benign phyllodes tumors 55.1%(n=98). Maximum number of cases were of the age groups 30-39 years (36.5%(n=65). Two cases of malignant phyllodes tumor were noted in age groups 11-20 years. Conclusion: Phyllodes tumor of breast is more common in 3rd decade. A multidisciplinary approach including complete and thorough clinical examination, careful histopathologic evaluation should be done to ensure prompt treatment to patients. Keywords: Phyllodes tumor, Fibroepithelial lesion, Histopathologic examination